Evidence-bases Economy in Medical Diagnosis; a Letter To Editor - Hashemi, Reza (Archives of Men’s Health, 2023)
After history taking, physical examination, and making a list of clinical diagnosis, laboratory tests and imaging are necessary for ruling out differential diagnosis, which is a multifaceted scientific, economic, and ethical decision. In this article, we focus on the economic sector and introduce a new, evidence-based method for this purpose.